2021
DOI: 10.1155/2021/3565360
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Alleviated Potassium Dichromate-Induced Oxidative Stress and Reprotoxicity in Male Rats

Abstract: Melatonin (ML) is a potent antioxidant that reduces oxidative stress. This study was designed to examine the protective effect of melatonin on potassium dichromate- (PDC-) induced male reproductive toxicity. Forty rats were divided into five groups: the control group, rats administered PDC orally (10 mg/kg body weight) for eight weeks, rats administered ML intraperitoneally at doses of either 2.5 or 5 mg/kg followed by the administration of PDC, and rats administered 5 mg/kg ML only. The treatment of rats with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 58 publications
5
23
0
Order By: Relevance
“…In the current study, at 15 mg/kg/b.wt of POD-intoxicated group III, SOD, GST, and GSH-Px showed a significant decrease compared to control group I (Table 1). These results agree with those of Bashandy et al [28], who showed that daily oral POD treatment for eight weeks in rats caused oxidative stress and a significant reduction in SOD, CAT, and GSH-Px. Additionally, our findings align with those of Kotyk and Iskra [29], who declared that the i.p.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the current study, at 15 mg/kg/b.wt of POD-intoxicated group III, SOD, GST, and GSH-Px showed a significant decrease compared to control group I (Table 1). These results agree with those of Bashandy et al [28], who showed that daily oral POD treatment for eight weeks in rats caused oxidative stress and a significant reduction in SOD, CAT, and GSH-Px. Additionally, our findings align with those of Kotyk and Iskra [29], who declared that the i.p.…”
Section: Discussionsupporting
confidence: 93%
“…These results agree with those of Bashandy et al. [ 28 ], who showed that daily oral POD treatment for eight weeks in rats caused oxidative stress and a significant reduction in SOD, CAT, and GSH-Px. Additionally, our findings align with those of Kotyk and Iskra [ 29 ], who declared that the i.p.…”
Section: Discussionsupporting
confidence: 93%
“…Mice, rats, and hamsters were the subjects of 13 ( 35 38 , 43 51 ), 24 ( 17 , 39 – 42 , 52 70 ), and one ( 71 ) studies, respectively. Studies have utilized heavy metals (n= 12) including arsenic ( 37 , 45 , 67 ), lead ( 58 ), cadmium ( 42 , 47 , 48 , 55 , 68 , 69 ), Hexavalent chromium ( 38 ), and Potassium dichromate ( 52 ) and toxic materials (n= 26) including sodium fluoride (NaF) ( 61 ), 2-Bromopropane ( 54 ), Bisphenol A ( 17 , 43 , 46 , 59 , 62 , 63 , 70 ), thioacetamide ( 56 ), Bisphenol S ( 71 ), ochratoxin A ( 57 ), nicotine ( 49 ), Cigarette smoke ( 39 ), diazinon ( 35 , 36 , 50 ), formaldehyde ( 40 , 60 ), bis(2-ethylhexyl) phthalate (DEHP) ( 44 ), carbon tetrachloride (CCl4) ( 41 , 53 ), Chlorpyrifos ( 65 , 66 ), nonylphenol ( 64 ), and acetamiprid ( 51 ) to induce oxidative stress. To administer the stressors, oral (n= 19) ( 37 , 44 – 46 , 51 , 52 , 57 – 59 , 63 – 72 ), intraperitoneal (n= 14, IP) ( 35 , 36 , 38 , 40 –…”
Section: Resultsmentioning
confidence: 99%
“…Studies have utilized heavy metals (n= 12) including arsenic ( 37 , 45 , 67 ), lead ( 58 ), cadmium ( 42 , 47 , 48 , 55 , 68 , 69 ), Hexavalent chromium ( 38 ), and Potassium dichromate ( 52 ) and toxic materials (n= 26) including sodium fluoride (NaF) ( 61 ), 2-Bromopropane ( 54 ), Bisphenol A ( 17 , 43 , 46 , 59 , 62 , 63 , 70 ), thioacetamide ( 56 ), Bisphenol S ( 71 ), ochratoxin A ( 57 ), nicotine ( 49 ), Cigarette smoke ( 39 ), diazinon ( 35 , 36 , 50 ), formaldehyde ( 40 , 60 ), bis(2-ethylhexyl) phthalate (DEHP) ( 44 ), carbon tetrachloride (CCl4) ( 41 , 53 ), Chlorpyrifos ( 65 , 66 ), nonylphenol ( 64 ), and acetamiprid ( 51 ) to induce oxidative stress. To administer the stressors, oral (n= 19) ( 37 , 44 – 46 , 51 , 52 , 57 – 59 , 63 – 72 ), intraperitoneal (n= 14, IP) ( 35 , 36 , 38 , 40 – 42 , 47 50 , 54 , 56 , 60 , 62 ), and subcutaneous (n= 2, SQ) ( 55 , 63 ) routes were used. To administer melatonin, oral (n= 9) ( 37 , …”
Section: Resultsmentioning
confidence: 99%
“…Spleen cells have also been found to contain melatonin receptors (MT2) [43]. In rodents, including mice, voles, and hamsters, external administration of melatonin has been shown to stimulate the proliferation of spleen cells, with MT2 receptors playing a significant part in this stimulatory impact of melatonin [44]. Treatment with melatonin also promotes T cell proliferation [45].…”
Section: Effects Of Melatonin On the Immune System In Covid-19mentioning
confidence: 99%